Short-term extreme ice loads prediction and fatigue damage evaluation for an icebreaker. (30th April 2018) - Chai, Wei; Leira, Bernt J.; Naess, Arvid
ABSTRACT: In this paper, the short-term extreme value statistics of the ice loads acting on ship hull and the fatigue damage due to ice loads actions are studied. Due to the stochastic nature of the ice-induced loads and randomness of the ice thickness, probabilistic methods and models are applied in order to find some correlations between the ice-induced loads statistics and the prevailing ice conditions. For the extreme value prediction, the average conditional exceedance rate method is applied to approximate the exact extreme value distribution. The short-term fatigue damage is estimated based on the S–N curve approach. Furthermore, probabilistic models, such as the Weibull distribution and the three-parameter exponential distribution are applied to approximate the distribution of the stress ranges due to ice loads actions and the performance of the fatigue damage evaluation based on probabilistic distribution functions of the stress ranges is studied.